Perlindungan Hukum Terhadap Korban Kejahatan Perang: Perspektif Hukum Humaniter Internasional - Muhamad Wildan; Fatih Arif Mutaqin (Lembaga Pengembangan Kinerja Dosen, 2024)
People who are not involved in war receive legal protection, as regulated in Article 3 of the 1949 Geneva Convention. People who are protected include combatants, militia members and civilians, but the protection has not been implemented properly, because violence often occurs against they. This writing explains the protection of people who are not involved in war, but this protection is still far from what it should be because violence still occurs against civilians who are victims of inhumane actions.